Synthesis and Characterization of High Surface Area Nano Titanium Dioxide - Ahmed, Dalya J. Ahmed; Al-abdaly, Basim I.; Hussein, Sattar J. (Journal of Petroleum Research and Studies, 2021)
TiO2 and TiO2-Al2O3 nanoparticles were synthesized via sol-gel method using hydrolysis of Titanium tetraisopropoxide (TTIP) with ethanol and water mixture as titania source. TiO2-Al2O3 Nano-composite was successfully synthesized using the sol-gel technique. Tetraisopropoxide and aluminium isopropoxide were used to prepare TiO2-Al2O3. All prepared samples calcination were conducted at different temperature (400 to 700) oC. The synthesized TiO2 and TiO2-Al2O3 nanocomposites were then characterized by XRD, AFM, BET surface area, SEM, XRF. XRD, the analysis showed that the presence of alumina (Al2O3) in the TiO2 has an effect on crystal size, particles size, surface area, and crystal phases; The XRD result revealed that the prepared TiO2 nanoparticles were anatase phase at 400oC, and 500oC, and transformed to rutile from 600oC to 700oC, but after addition of alumina TiO2 was of anatase phase, without any rutile at all calcination temperatures, also, the addition of alumina leads to a significant decrease in the crystal size, particles size, especially at high temperatures while the surface area of pure titanium was increased, and this corresponds to the results of the AFM and SEM. The best-obtained surface area was 355.18 m2/ gm. with 34.98 nm of average particle size at 500oC in comparison with pure nano titanium dioxide